Are physicians and clinical pharmacists aware and knowledgeable enough about inappropriate prescribing for elderly patients? Findings from Malaysia - Akkawi, Muhammad Eid; Nik Mohamed, Mohamad Haniki (European Association of Hospital Pharmacists (EAHP), 2018)
Objectives To assess the knowledge of physicians and clinical pharmacists about inappropriate prescribing for elderly patients, their confidence in prescribing for elderly patients, and their perceptions of barriers to appropriate prescribing in this population.